PROJECT SUCCESS, STAKEHOLDERS AND COLLABORATION: A LITERATURE REVIEW - Dantas, Aline Soares (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2022)
Project success, stakeholders, and collaboration are studied in the project management literature. Research relating to the three themes is scarce, and managers are increasingly pressured to improve the results of their projects. The general objective is to verify how the themes are applied in publications until October 2020. The methodology used was a literature review in the Scopus, Web of Science, and Science Direct databases based on the criteria used. Forty articles were selected and analyzed by content analysis. Publications are dispersed and distributed mainly in journals focused on Project Management, Engineering, and Management. There is a predominance of quantitative and concentrated studies in the area of Construction. Over the years, it can be concluded there has been an increase in the number of criteria and stakeholders used to assess success, and collaboration has become essential for improving results.